Single-molecule sensing of peptides and nucleic acids by engineered aerolysin nanopores - Chan Cao (Nature Portfolio, 2019)
Aerolysin pores have potential to improve the accuracy of DNA sequencing and single-molecule proteomics. Here, the authors rationally design a set of mutated pores to achieve a more accurate detection of peptides and nucleic acids.